(untitled) (Eurasian Journal of Learning and Academic Teaching, 2022)
Currently, the development of new theories and practices of physical education, including the upbringing of children and adolescents, their socio-pedagogical support and protection is a process that is considered an integral part of individual-oriented integrated physical education.